The intersection of transnational and international criminal law – example of trafficking in persons - Głogowska-Balcerzak, Anna (Review of European and Comparative Law, 2022)
The paper addresses the possible intersection of transnational and international criminal law, using the example of the crime of trafficking in persons. In recent years traf- ficking in persons has gathered a great deal of attention from scholars, practitioners and politicians, nevertheless theoretical aspects concerning that notion and its relation with other concepts present in international law – such as slavery, practices similar to slavery, enslavements etc . – have still been neglected . As this notion appears at the intersection of different areas of law, including transnational and international criminal law, its closer analysis can contribute to determination of theoretical boundaries of both areas of international law.